Effects of transcutaneous electrical nerve stimulation and cryotherapy on pain threshold by induced pressure - Lairton Fabricio de Menezes Maciel; Jose Jamacy de Almeida Ferreira; Heleodorio Honorato dos Santos; Palloma Rodrigues de Andrade (Universidade de São Paulo, 2014)
Studies have shown that cryotherapy, transcutaneous electrical nerve stimulation (TENS) and the association of them promotes analgesia, but the effectiveness of this association is unclear. The objective was to evaluate the effects of single and combined application of TENS and cryotherapy on pressure-induced pain threshold in healthy subjects. The sample consisted of 40 subjects, randomly assigned into four groups: (1) cryotherapy group - CG, (2) TENS group - GT; (3) cryotherapy + TENS group - GCT; (4) placebo group - GP. The pain threshold was determined by an algometer before (T1), immediately after (T2) and in the instants 10 (T3), 20 (T4) and 30 (T5) minutes after application of the analgesic techniques. TENS (100 Hz, 40 μs) and cryotherapy (cold compress) were applied for 20 minutes in the GC, GT and GTC, while in the GP was simulated electrical stimulation for the same period of time. Repeated measures ANOVA and Bonferroni post hoc test were employed, considering a significance level of 5%. All experimental groups showed an increase in pain threshold when compared to GP: GC (p<0.001), GT (p<0.009) and GCT (p<0.008). In relation to the time of analgesia, there was an increase in pain threshold in T2 for all experimental groups (p <0.001) up T3 to GCT (p <0.001) and only in the GC analgesia lasted up to T5. We concluded that under the conditions studied, the three experimental groups had an increase in pain threshold compared to the GP, but cryotherapy had more prolonged effect.